ZSM-57 molecular sieve as well as preparation method and application thereof
Through a simplified preparation method, mixing and crystallizing the specific ratios of silicon source, alkali source, aluminum source and template agent is used to perform mixing and crystallization, which solves the problems of complex preparation of existing ZSM-57 molecular sieve and limited catalytic cracking capabilities, achieving low-cost and efficient catalytic cracking effect.
Patent Information
- Application Number
- CN202311435829.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The preparation process of the existing ZSM-57 molecular sieve is complex in operation, high in cost, and has limited catalytic cracking capabilities.
A simplified preparation method is adopted, including mixing a silicon source with an alkaline source, followed by adding an aluminum source, a template agent and water for crystallization. The template agent is a reaction mixture of 1,5-dibromopentane and triethylamine. The weight ratio of the silicon source to the template agent is between 0.14 and 0.35, and the molar ratio of the alkali source, aluminum source and water is between 0.15 and 0.4:0.01 and 0.025:1:15 and 80.
The preparation process of ZSM-57 molecular sieve is simplified, the synthesis cost is reduced, and its catalytic cracking capacity is significantly improved, especially in the n-octane reaction.
Smart Images

Figure CN119911935A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of inorganic materials, and in particular, to a ZSM-57 molecular sieve and a preparation method and application thereof. Background Art
[0002] ZSM-57 molecular sieve is a molecular sieve with a two-dimensional ten-membered ring and eight-membered ring pore structure. Its pore diameter (5.4×5.1, 3.3×4.8) is slightly smaller than that of ZSM-5, and has application prospects in small molecule shape-selective catalysis. The existing preparation process of ZSM-57 molecular sieve has defects such as complex operation process and high preparation cost, and the catalytic cracking ability of ZSM-57 molecular sieve prepared by the existing process still has room for improvement. Summary of the invention
[0003] The purpose of the present disclosure is to provide a ZSM-57 molecular sieve and a preparation method and application thereof, so as to simplify the preparation process, reduce the synthesis cost and improve the catalytic cracking ability of the ZSM-57 molecular sieve.
[0004] In order to achieve the above object, the present disclosure provides a method for preparing ZSM-57 molecular sieve in a first aspect, the method comprising:
[0005] Performing a first mixing of a silicon source and an alkali source to obtain a first mixture;
[0006] mixing an aluminum source, a template, and optionally water with the first mixture to obtain a second mixture;
[0007] performing a crystallization treatment on the second mixture to obtain a crystallized product;
[0008] The template is a reaction mixture of 1,5-dibromopentane and triethylamine, and the weight ratio of the template to the silicon source is (0.14-0.35):1; calculated as oxides, the molar ratio of the alkali source, aluminum source, silicon source and water is (0.15-0.4):(0.01-0.025):1:(15-80).
[0009] Optionally, the weight ratio of the template to the silicon source is (0.24-0.35):1; calculated as oxides, the molar ratio of the alkali source, aluminum source, silicon source and water is (0.17-0.3):(0.015-0.023):1:(24-40).
[0010] Optionally, the preparation step of the template comprises:
[0011] Mixing 1,5-dibromopentane and triethylamine and reacting them in the presence of a solvent to obtain the template;
[0012] Wherein, the weight ratio of 1,5-dibromopentane to triethylamine is 1:(1.5-2.5);
[0013] The reaction conditions include: temperature of 60 to 80° C. and time of 5 to 20 hours.
[0014] Optionally, the solvent is at least one selected from methanol, ethanol, propanol, butanol and ethylene glycol.
[0015] Optionally, the silicon source is one or more selected from silica sol, water glass, ethyl orthosilicate, white carbon black and silica gel;
[0016] The aluminum source is one or more selected from aluminum nitrate, aluminum chloride, aluminum sulfate, sodium aluminate and polyaluminum chloride;
[0017] The alkali source is one or more selected from sodium hydroxide, potassium hydroxide and ammonia water.
[0018] Optionally, the first mixing conditions include: a stirring speed of 50 to 100 r / min and a time of 0.5 to 2 hours;
[0019] The second mixing conditions include: a stirring speed of 80 to 120 r / min and a time of 1 to 4 hours.
[0020] Optionally, the crystallization treatment conditions include: a temperature of 140 to 180° C. and a time of 5 to 7 days.
[0021] Optionally, the method further comprises: drying and first calcining the crystallized product to obtain a first calcined material, contacting the first calcined material with a phosphorus-containing compound to perform phosphorus ion exchange, and then performing a second calcination.
[0022] Optionally, the phosphorus-containing compound is at least one selected from diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphoric acid and hypophosphorous acid;
[0023] Calculated as oxide, the molar ratio of the phosphorus-containing compound to the aluminum source is (0.01-1.5):1.
[0024] Optionally, the drying conditions include: a temperature of 50 to 120° C. and a time of 6 to 24 hours;
[0025] The first calcination conditions include: a temperature of 400 to 700° C. and a time of 1 to 10 hours;
[0026] The conditions of the second calcination include: a temperature of 400 to 700° C. and a time of 1 to 10 hours.
[0027] In a second aspect of the present disclosure, a ZSM-57 molecular sieve prepared by the method described in the first aspect of the present disclosure is provided.
[0028] In a third aspect of the present disclosure, there is provided application of the ZSM-57 molecular sieve described in the second aspect of the present disclosure in a catalytic cracking reaction of n-octane.
[0029] Through the above technical scheme, the preparation process of the ZSM-57 molecular sieve disclosed in the present invention is simple, the amount of template agent used is small, the synthesis cost is low, and it is used for catalytic cracking of n-octane and shows a high cracking ability.
[0030] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0032] Figure 1 is the XRD spectrum of the ZSM-57 molecular sieve prepared in Example 1.
[0033] Figure 2 This is a SEM photograph of the ZSM-57 molecular sieve prepared in Example 1.
[0034] Figure 3 is the template used in Example 1 13 C NMR spectrum.
[0035] Figure 4 is the template used in Example 1 1 H NMR spectrum. DETAILED DESCRIPTION
[0036] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0037] In a first aspect of the present disclosure, a method for preparing a ZSM-57 molecular sieve is provided, the method comprising the following steps S1 to S3:
[0038] S1, mixing a silicon source and an alkali source for the first time to obtain a first mixture;
[0039] S2, mixing an aluminum source, a template, and optionally water with the first mixture to obtain a second mixture;
[0040] S3, crystallizing the second mixture to obtain a crystallized product;
[0041] The template is a reaction mixture of 1,5-dibromopentane and triethylamine, and the weight ratio of the template to the silicon source is (0.14-0.35):1; calculated as oxides, the molar ratio of the alkali source, aluminum source, silicon source and water is (0.15-0.4):(0.01-0.025):1:(15-80).
[0042] In step S1, the silicon source and the alkali source may be mixed at room temperature.
[0043] The silicon source may be a common type in the art. Specifically, the silicon source may be one or more selected from silica sol, water glass, tetraethyl orthosilicate, white carbon black and silica gel.
[0044] The alkali source may be an alkali metal hydroxide and / or aqueous ammonia. Specifically, the alkali source may be selected from sodium hydroxide, potassium hydroxide and aqueous ammonia (NH 3 ·H 2 O) in one or more.
[0045] The first mixing conditions may include: a stirring speed of 50 to 100 r / min and a time of 0.5 to 2 hours.
[0046] In step S2, the template is a reaction mixture of 1,5-dibromopentane and triethylamine, which refers to a mixture obtained by reacting 1,5-dibromopentane and triethylamine, and its components may contain N,N,N,N',N',N'-hexaethylpentane diamine bromide, 1,5-dibromopentane, triethylamine, etc.
[0047] In one embodiment, the preparation step of the template comprises: mixing 1,5-dibromopentane with triethylamine and reacting in the presence of a solvent to obtain the template. The template thus obtained does not require extraction, recrystallization and other processes, is simple and easy to obtain and has low cost. The template can be used to prepare the ZSM-57 molecular sieve disclosed in the present invention with a low amount of template. Wherein, the weight ratio of 1,5-dibromopentane to triethylamine is 1: (1.5-2.5), preferably 1: (2-2.5). The reaction conditions may include: a temperature of 60-80°C and a time of 5-20 hours. The solvent may be at least one selected from methanol, ethanol, propanol, butanol and ethylene glycol. The amount of the solvent can be adjusted within a certain range, specifically, the weight ratio of 1,5-dibromopentane to the solvent can be 1: (0.02-0.5).
[0048] The aluminum source is an aluminum-containing compound. Specifically, the aluminum source can be an aluminum salt, such as aluminum nitrate, aluminum chloride, aluminum sulfate, sodium aluminate, etc., or industrial polyaluminum chloride, etc., or one or more mixtures of aluminum salts and polyaluminum chloride.
[0049] The second mixing conditions may include: a stirring speed of 80 to 120 r / min and a time of 1 to 4 hours.
[0050] In a preferred embodiment, the weight ratio of the template to the silicon source is (0.24-0.35):1; calculated as oxides, the molar ratio of the alkali source, aluminum source, silicon source and water is (0.17-0.3):(0.015-0.023):1:(24-40).
[0051] In step S3, the conditions of the crystallization treatment may include: a temperature of 140 to 180° C., preferably 150 to 170° C., and a time of 5 to 7 days, preferably 5 to 6 days. The crystallization treatment may be performed in a sealed state.
[0052] According to the present disclosure, in order to improve the aging stability of the ZSM-57 molecular sieve, the method further includes the following step S4:
[0053] S4, drying and first calcining the crystallized product to obtain a first calcined material, contacting the first calcined material with a phosphorus-containing compound to perform phosphorus ion exchange, and then performing a second calcination.
[0054] The phosphorus-containing compound may be at least one selected from diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphoric acid and hypophosphorous acid; the molar ratio of the phosphorus-containing compound to the aluminum source may be (0.15-1.5):1, preferably (0.2-1.5):1, calculated as oxide. The phosphorus ion exchange may be performed by an impregnation method.
[0055] Furthermore, the drying conditions may include: a temperature of 50 to 120° C. and a time of 6 to 24 hours; the first roasting conditions may include: a temperature of 400 to 700° C. and a time of 1 to 10 hours; the second roasting conditions may include: a temperature of 400 to 700° C. and a time of 1 to 10 hours.
[0056] In a second aspect of the present disclosure, a ZSM-57 molecular sieve prepared by the method described in the first aspect of the present disclosure is provided. The BET specific surface area of the ZSM-57 molecular sieve may be 320 to 370 m 2 / g, preferably 340 to 370 m 2 / g; the micropore specific surface area can be 290~340m 2 / g, preferably 300 to 340 m 2 / g; the pore volume can be 0.200~0.275cm 3 / g, preferably 0.210 to 0.275 cm 3 / g; the micropore volume can be 0.120~0.170cm3 / g, preferably 0.140 to 0.170 cm 3 / g. The molar ratio of silicon to aluminum atoms in the ZSM-57 molecular sieve may be 17 to 30. In one embodiment, P 2 O 5 The phosphorus content of the ZSM-57 molecular sieve is 0.15 to 0.7 weight % based on the dry weight of the ZSM-57 molecular sieve.
[0057] In a third aspect of the present disclosure, there is provided application of the ZSM-57 molecular sieve described in the second aspect of the present disclosure in a catalytic cracking reaction of n-octane.
[0058] The ZSM-57 molecular sieve disclosed in the present invention is used for catalytic cracking of n-octane and shows excellent catalytic activity and cracking ability. Specifically, the application may include: the cracking temperature is 500° C., 1 g of fresh molecular sieve sample is used, and the n-octane feed amount is 0.96 g.
[0059] The present disclosure is described in detail below in conjunction with embodiments, but the scope of the present disclosure is not limited thereby.
[0060] The reagents used in the following examples are all commercially available.
[0061] In the following examples, the template agent was detected by nuclear magnetic resonance spectroscopy, the experimental instrument was Bruker AVANCEⅢ600WB nuclear magnetic resonance spectrometer, the experimental method was a solid double resonance probe, mm ZrO2 rotor. The resonance spectrum detected by 13C is 125.74MHz, with 1H decoupling power of 80kHz, 1H excitation pulse width of 2.65μs, and scan times of 6000 times.
[0062] The ZSM-57 molecular sieve was tested using the Quantachrome AS-6B physical adsorption instrument. The experimental method was as follows: the sample was heated to 300°C for degassing for 4 hours under a vacuum of 1.3Pa, and nitrogen was passed through at 77K to reach static adsorption equilibrium. The amount of nitrogen adsorbed by the adsorbent was calculated based on the difference between the amount of nitrogen inlet and the amount remaining in the gas phase after adsorption. The specific surface area was calculated using the BET formula, and the nitrogen adsorption amount corresponding to P / P0=0.98 was taken; the pore volume was calculated according to the liquid adsorption system.
[0063] Example 1
[0064] (1) Dissolve 1,5-dibromopentane in butanol solution, then add triethylamine, and react at 80°C for 10 hours to obtain a template, wherein the weight ratio of 1,5-dibromopentane, butanol, and triethylamine is 1:0.3:2.1. 13 C NMR spectrum is shown in Figure 3, the spectrum is characterized by seven carbon species with different chemical environments, 1 H NMR spectrum is shown in Figure 4 The spectrum corresponds to the hydrogen species composition characteristics of 6 different chemical environments, indicating that the obtained template is a mixture containing components such as N,N,N,N',N',N'-hexaethylpentane diamine bromide.
[0065] (2) At room temperature, silica sol (SiO 2 The mixture was mixed with NaOH and stirred at a stirring speed of 100 r / min for 1 hour; then sodium aluminate, the template in step (1) and water were added and stirred at a stirring speed of 120 r / min for 4 hours to obtain a mixture, wherein the weight ratio of the template to the silica sol was 0.34:1, and the Na 2 O: A1 2 O 3 :SiO 2 :H 2 O=0.2:0.021:1:24; then the obtained mixture was placed in a high pressure reactor for crystallization at 160°C for 6 days. The cooled crystallized product was vacuum filtered, washed with deionized water, dried at 120°C for 5 hours, and then first calcined at 550°C for 6 hours; then the calcined material was contacted with diamine hydrogen phosphate for impregnation (P 2 O 5 / A1 2 O 3 The molar ratio is 0.5), and after impregnation, a second calcination is performed at 550°C for 6 hours to obtain a ZSM-57 molecular sieve, and its XRD spectrum is shown in Figure 1 The spectrum has diffraction peaks at the following positions: 2θ=7.7°, 9.4°, 12.7°, 15.3°, 23.4°, 24.9°, 29.3°, which is consistent with the characteristic peaks of ZSM-57 molecular sieve. See SEM picture Figure 2 , it can be seen that the ZSM-57 molecular sieve is in the form of flakes. The specific surface area and other data of the ZSM-57 molecular sieve are shown in Table 1.
[0066] Example 2
[0067] The ZSM-57 molecular sieve was prepared according to the method of Example 1, except that in step (2), the silicon source was silica gel (SiO 2 The content is 30% by weight), the aluminum source is aluminum nitrate, the alkali source is KOH, the weight ratio of the template to the silica gel is 0.3:1, and Na 2 O: A1 2 O 3 :SiO 2 :H 2O = 0.25: 0.017: 1: 40, the crystallization temperature is 170 ° C, and the time is 5 days. The XRD spectrum of the ZSM-57 molecular sieve is similar to Figure 1 Similarly, data such as specific surface area are shown in Table 1.
[0068] Example 3
[0069] The ZSM-57 molecular sieve was prepared according to the method of Example 1, except that in step (2), the silicon source was silica sol (SiO 2 The content is 30% by weight), the aluminum source is sodium aluminate, the alkali source is NaOH, the weight ratio of the template to the silica sol is 0.28:1, and Na 2 O: A1 2 O 3 :SiO 2 :H 2 O = 0.4: 0.012: 1: 20, the crystallization temperature is 160 ° C, and the time is 6 days. The XRD spectrum of the ZSM-57 molecular sieve is similar to Figure 1 Similarly, data such as specific surface area are shown in Table 1.
[0070] Example 4
[0071] The ZSM-57 molecular sieve was prepared according to the method of Example 1, except that in step (2), the silicon source was silica sol (SiO 2 The content is 30% by weight), the aluminum source is aluminum nitrate, the alkali source is NaOH, the weight ratio of the template to the silica sol is 0.26:1, and Na 2 O: A1 2 O 3 :SiO 2 :H 2 O = 0.4: 0.025: 1: 80, the crystallization temperature is 160 ° C, and the time is 6 days. The XRD spectrum of the ZSM-57 molecular sieve is similar to Figure 1 Similarly, data such as specific surface area are shown in Table 1.
[0072] Example 5
[0073] The ZSM-57 molecular sieve was prepared according to the method of Example 1, except that in step (2), the silicon source was silica sol (SiO 2 The content is 30% by weight), the aluminum source is aluminum nitrate, the alkali source is NaOH, the weight ratio of the template to the silica sol is 0.22:1, and Na 2 O: A1 2 O 3 :SiO 2 :H 2 O = 0.25: 0.017: 1: 35, the crystallization temperature is 140 ° C, and the time is 7 days. The XRD spectrum of the ZSM-57 molecular sieve is similar to Figure 1 Similarly, data such as specific surface area are shown in Table 1.
[0074] Example 6
[0075] The ZSM-57 molecular sieve was prepared according to the method of Example 1, except that in step (1), the weight ratio of 1,5-dibromopentane, butanol and triethylamine was 1:0.02:1.5. The XRD spectrum of the ZSM-57 molecular sieve was Figure 1 Similarly, data such as specific surface area are shown in Table 1.
[0076] Example 7
[0077] The ZSM-57 molecular sieve was prepared according to the method of Example 1, except that in step (2), phosphorus ion exchange was not performed, and the material after the first calcination was used as the molecular sieve product. The XRD spectrum of the ZSM-57 molecular sieve is Figure 1 Similarly, data such as specific surface area are shown in Table 1.
[0078] Comparative Example 1
[0079] The initial gel was prepared according to the following molar ratio: SiO 2 / Al 2 O 3 =100,OH - / SiO 2 =0.4, R / SiO 2 =0.2, H 2 O / SiO 2 =30, dissolve sodium aluminate, potassium hydroxide, 1,5-hexaethylpentanediammonium bromide in deionized water, and then add white carbon black under constant stirring. Then, put the above mixture into a 100ml crystallization kettle and react at 160°C for 168 hours. The cooled reaction solution was placed in a water bath for 5 hours, and after obvious stratification, the lower beige solid was ZSM-57 zeolite, which was separated, washed, dried, and roasted (roasting temperature 550°C, roasting time 8 hours) to obtain ZSM-57 molecular sieve. The particle size of the ZSM-57 molecular sieve is 2μm, the thickness is about 20nm, and the specific surface area and other data are shown in Table 1.
[0080] Table 1
[0081] Example <![CDATA[S BET (m 2 / g)]]> <![CDATA[Smicro(m 2 / g)]]> <![CDATA[Vtotal(cm 3 / g)]]> <![CDATA[Vmicro(cm 3 / g)]]> Example 1 368.0 338.8 0.266 0.157 Example 2 366.9 332.0 0.218 0.159 Example 3 341.7 306.0 0.232 0.141 Example 4 355.0 326.9 0.216 0.151 Example 5 348.3 315.7 0.209 0.144 Example 6 320.1 298.5 0.201 0.129 Example 7 370.5 341.2 0.269 0.161 Comparative Example 1 400.1 316.5 0.211 0.149
[0082] Test Example 1
[0083] The molecular sieves of the embodiment and the comparative example were used in the n-octane cracking evaluation test. The cracking reaction was carried out at 500°C, using 1g of fresh molecular sieve sample and 0.96g of n-octane feed. The n-octane conversion rate was calculated according to the following formula, and the evaluation data is shown in Table 2.
[0084] n-Octane conversion rate = weight of n-octane consumed in the reaction / weight of n-octane input × 100%
[0085] Table 2
[0086]
[0087]
[0088] As can be seen from Table 2, the ZSM-57 molecular sieve disclosed in the present invention is used for catalytic cracking of n-octane and exhibits a higher cracking ability.
[0089] Test Example 2
[0090] The samples of Example 1 and Example 7 were subjected to hydrothermal aging at 800° C. for 17 h, and the n-octane cracking evaluation test was performed according to the conditions of Test Example 1. The evaluation data are shown in Table 3.
[0091] Table 3
[0092] Conversion rate, weight % Example 1 72.7 Example 7 42.5
[0093] It can be seen from Table 3 that the ZSM-57 molecular sieve obtained after phosphorus ion exchange has good aging stability.
[0094] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings. However, the present disclosure is not limited to the specific details of the above embodiments. Within the technical concept of the present disclosure, the technical solution of the present disclosure can be subjected to a variety of simple modifications, and these simple modifications all belong to the protection scope of the present disclosure.
[0095] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0096] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing ZSM-57 molecular sieve, characterized in that: The method includes: Performing a first mixing of a silicon source and an alkali source to obtain a first mixture; mixing an aluminum source, a template, and optionally water with the first mixture to obtain a second mixture; performing a crystallization treatment on the second mixture to obtain a crystallized product; The template is a reaction mixture of 1,5-dibromopentane and triethylamine, and the weight ratio of the template to the silicon source is (0.14-0.35):1; calculated as oxides, the molar ratio of the alkali source, aluminum source, silicon source and water is (0.15-0.4):(0.01-0.025):1:(15-80).
2. The method according to claim 1, wherein: The weight ratio of the template to the silicon source is (0.24-0.35):1; calculated as oxides, the molar ratio of the alkali source, the aluminum source, the silicon source and water is (0.17-0.3):(0.015-0.023):1:(24-40).
3. The method according to claim 1, wherein: The preparation steps of the template include: Mixing 1,5-dibromopentane and triethylamine and reacting them in the presence of a solvent to obtain the template; Wherein, the weight ratio of 1,5-dibromopentane to triethylamine is 1:(1.5-2.5); The reaction conditions include: temperature of 60 to 80° C. and time of 5 to 20 hours.
4. The method according to claim 3, wherein: The solvent is at least one selected from methanol, ethanol, propanol, butanol and ethylene glycol.
5. The method according to claim 1, wherein: The silicon source is one or more selected from silica sol, water glass, tetraethyl orthosilicate, white carbon black and silica gel; The aluminum source is one or more selected from aluminum nitrate, aluminum chloride, aluminum sulfate, sodium aluminate and polyaluminum chloride; The alkali source is one or more selected from sodium hydroxide, potassium hydroxide and ammonia water.
6. The method according to claim 1, wherein: The first mixing conditions include: stirring speed of 50 to 100 r / min, time of 0.5 to 2 hours; The second mixing conditions include: a stirring speed of 80 to 120 r / min and a time of 1 to 4 hours.
7. The method according to claim 1, wherein: The conditions of the crystallization treatment include: a temperature of 140 to 180° C. and a time of 5 to 7 days.
8. The method according to claim 1, wherein: The method further comprises: drying and first calcining the crystallized product to obtain a first calcined material, contacting the first calcined material with a phosphorus-containing compound to perform phosphorus ion exchange, and then performing a second calcination.
9. The method according to claim 8, wherein: The phosphorus-containing compound is at least one selected from diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphoric acid and hypophosphorous acid; Calculated as oxide, the molar ratio of the phosphorus-containing compound to the aluminum source is (0.01-1.5):
1.
10. The method according to claim 8, wherein: The drying conditions include: a temperature of 50 to 120° C. and a time of 6 to 24 hours; The first calcination conditions include: a temperature of 400 to 700° C. and a time of 1 to 10 hours; The conditions of the second calcination include: a temperature of 400 to 700° C. and a time of 1 to 10 hours.
11. ZSM-57 molecular sieve prepared by the method according to any one of claims 1 to 10.
12. Use of the ZSM-57 molecular sieve according to claim 11 in catalytic cracking of n-octane.
Citation Information
Patent Citations
Process for manufacturing molecular sieve of mfs framework type and its use
CN101384361A
Mesoporous molecular sieve and preparation method and application thereof
CN111097480A
Multi-component molecular sieve catalyst compositions and their use in aromatics reactions
US20040097770A1